Nfat1 Regulates Adult Articular Chondrocyte Function through Its Age-Dependent Expression Mediated by Epigenetic Histone Methylation - Rodova, Marianna (2011)
The development of disease-modifying pharmacologic therapy for osteoarthritis (OA) currently faces major obstacles, largely because the regulatory mechanisms for the function of adult articular chondrocytes remain unclear. We previously demonstrated that lack of Nfat1, one of the NFAT (nuclear factor of activated T cells) transcription factors, causes OA-like changes in adult mice. This study aimed to identify whether Nfat1 specifically regulates adult articular chondrocyte function and its age-dependent regulatory mechanism using both Nfat1-deficient and wild-type mice. Deletion of Nfat1 did not induce OA-like articular chondrocyte dysfunction (e.g., overexpression of proinflammatory cytokines and matrixdegrading proteinases) until the adult stage. RNAi-mediated Nfat1 knockdown caused dysfunction of wild-type adult articular chondrocytes. Nfat1 expression in wild-type articular chondrocytes was low in the embryonic, but high in the adult stage. Chromatin immunoprecipitation assays demonstrated that an increase in Nfat1 expression in articular chondrocytes was associated with increased H3K4me2 (a histone modification linked to transcriptional activation); while a decrease in Nfat1 expression in articular chondrocytes was correlated with increased H3K9me2 (a histone modification linked to transcriptional repression). Knockdown of lysine-specific demethylase-1 (Lsd1) in embryonic articular chondrocytes up-regulated Nfat1 expression concomitant with increased H3K4me2 at the Nfat1 promoter. Knockdown of Jmjc-containing histone demethylase-2a (Jhdm2a) in 6-month articular chondrocytes down-regulated Nfat1 expression concomitant with increased H3K9me2 at the Nfat1 promoter. These results suggest that Nfat1 is an essential transcriptional regulator of chondrocyte homeostasis in adult articular cartilage. Age-dependent Nfat1 expression in articular chondrocytes is regulated by dynamic histone methylation, one of the epigenetic mechanisms that regulate gene transcription.